TANTANGAN PENERAPAN KURIKULUM MERDEKA BELAJAR DALAM PEMBELAJARAN PAI DI SMAN 2 LIMBOTO - Nana Adelina Makalalag; Kamila Nangune; Yusnaini Yusnaini (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to identify challenges in implementing Merdeka Belajar Curriculum in Islamic Religious Education (PAI) learning at SMAN 2 Limboto. This research uses a qualitative approach with descriptive methods. Data were collected through interviews, observations, and document analysis related to the implementation of the Merdeka Curriculum. The results of this study indicate that the challenges in the application of independent learning in the independent curriculum in Islamic Religious Education learning at SMAN 2 Limboto School are the teacher's lack of understanding of the curriculum and the Lack of Readiness of Islamic Religious Education Teachers of SMAN 2 Limboto in Implementing the Independent Curriculum in the Learning Process